Analisis Ergonomi Produk Meja Rias di PT XYZ Menggunakan Pendekatan Antropometri - Ghaly Atha Maulana; Tranggono Tranggono (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
This research analyzes the dressing table products of PT XYZ using anthropometric methods, taking into consideration body measurements such as hip width, thigh length, seated body height, and elbow length. The primary objective is to assess the suitability of product dimensions with human body structure from an anthropometric perspective. The process of testing data uniformity involves calculating the average of observation results, standard deviation, and establishing upper and lower control limits with the coefficient value of k. Adequacy testing of data is conducted to evaluate the quantity of collected data. Subsequently, ideal dimensions for the dressing table product will be determined. The analysis results indicate significant differences between the initial dimensions and the ideal dimensions, concluding that adjustments to product dimensions are necessary. Therefore, it is recommended that PT XYZ make adjustments to the dimensions of the dressing table product based on anthropometric principles to enhance user comfort and customer confidence in the product.